"Inflamed" depression: A review of the interactions between depression and inflammation and current anti-inflammatory strategies for depression - Yishu Yin; Ting Ju; Deyong Zeng; Fangyuan Duan; Yuanbing Zhu; Junlian Liu; Yongzhi Li; Weihong Lu (Elsevier, 2024)
Depression is a common mental disorder, the effective treatment of which remains a challenging issue worldwide. The clinical pathogenesis of depression has been deeply explored, leading to the formulation of various pathogenic hypotheses. Among these, the monoamine neurotransmitter hypothesis holds a prominent position, yet it has significant limitations as more than one-third of patients do not respond to conventional treatments targeting monoamine transmission disturbances. Over the past few decades, a growing body of research has highlighted the link between inflammation and depression as a potential key factor in the pathophysiology of depression. In this review, we first summarize the relationship between inflammation and depression, with a focus on the pathophysiological changes mediated by inflammation in depression. The mechanisms linking inflammation to depression as well as multiple anti-inflammatory strategies are also discussed, and their efficacy and safety are assessed. This review broadens the perspective on specific aspects of using anti-inflammatory strategies for treating depression, laying the groundwork for advancing precision medicine for individuals suffering from "inflamed" depression.